2012
DOI: 10.2188/jea.je20110164
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Optimal Obesity Index Cutoffs for Predicting Development of Multiple Metabolic Risk Factors: The Korean Genome and Epidemiology Study

Abstract: BackgroundIn this prospective cohort study, we estimated the risk of developing more than 1 metabolic risk factor, using different obesity indices. In addition, we investigated the relative usefulness of the obesity indices for predicting development of such risk factors and calculated optimal cutoffs for the obesity indices.MethodsThe cohort comprised 10 038 representative residents of a small city and a rural county who were recruited in 2001–2002. Follow-up examinations were conducted every 2 years. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
4
29
1
Order By: Relevance
“…These findings support previous studies that suggest that ethnic variation among populations from different countries might require different anthropometric measurement cut-off points to diagnose obesity and its related diseases [13,25]. This decision was made because studies had confirmed that disease risk in Asian people was high at WC cut-off points below those defined in European populations [55][56][57]. Therefore, further research is essential to determine ethnic-specific anthropometric cutoff points for the Saudi Arabia population, which may potentially be beneficial in correctly identifying individuals at high risk for developing obesity and its related diseases.…”
Section: Association Of Family History Of Chronic Diseases With Genersupporting
confidence: 87%
“…These findings support previous studies that suggest that ethnic variation among populations from different countries might require different anthropometric measurement cut-off points to diagnose obesity and its related diseases [13,25]. This decision was made because studies had confirmed that disease risk in Asian people was high at WC cut-off points below those defined in European populations [55][56][57]. Therefore, further research is essential to determine ethnic-specific anthropometric cutoff points for the Saudi Arabia population, which may potentially be beneficial in correctly identifying individuals at high risk for developing obesity and its related diseases.…”
Section: Association Of Family History Of Chronic Diseases With Genersupporting
confidence: 87%
“…In our study, the WHtR cut-off values were higher than those in Japanese (2005-2007) [31] and Korean (2001) [32 ]men and women. We also noticed that the cut-off value of WHtR in women in Xinjiang was the same as in women in Guangdong, suggesting that WHtR may be a better universal indicator for the Chinese population.…”
Section: Discussioncontrasting
confidence: 60%
“…33 As for the Asian population, BMI, WHR, and WHtR values in both man and women of our study were higher than those in Japanese and Korean man and women. 34,35 We also noticed that cutoff values of BMI, WHR, WHtR, and TG/HDL in Uighur women were also higher than those in Chinese women in Guangdong. 5 It remains unclear why the cutoffs to detect the metabolic syndrome in a Uighur population were higher than those in Asian and African population and lower than those in the European population.…”
Section: Discussionmentioning
confidence: 70%